Penilaian Kinerja Keuangan 5 Perusahaan Perbankan Terbesar Periode 2010-2012 Menggunakan DuPont System - Lesmana, Theresia (Bina Nusantara University, 2013)
Assessment of corporate performance can be viewed from financial aspect and nonfinancial aspect. This study attempted specifically to measure financial performance by using the DuPont system of financial analysis. DuPont system disaggregates performance into three components. They are Net Profit Margin (NPM), Return on Assets (ROA) and Return on Equity (ROE). Object of this study is five largest financial institutions based on market capitalization and go public. Those five financial institutions are Bank Republik Indonesia (Persero) Tbk (BBRI), Bank Central Asia Tbk (BBCA), Bank Mandiri (Persero) Tbk (BMRI), Bank Negara Indonesia (Persero) Tbk (BBNI) and Bank Danamon Indonesia Tbk (BDMN). The financial performance of five banks was measured for three periods, from 2010 until 2012. It was found that only Bank Negara Indonesia (Persero) Tbk is the best financial performance using DuPont System.